The search for al Qaeda its leadership, ideology, and future - Riedel, Bruce O. (Brookings Institution Press, 2008)
"Profiles the most important figures in the al Qaeda movement---Osama bin Laden, Ayman Zawahiri, Abu Musaib al Zarqawi, and Mullah Omar, giving a comprehensive analysis of its origins, leadership, ideology, and strategy. Focuses more closely on what has happened to al Qaeda since 9/11 and outlines its ultimate goals"--Provided by publisher.